Power Grids with Renewable Energy: Storage, integration and digitalization - Sallam, Abdelhay A.; Malik, Om P. (IET Energy Engineering Series, 2021)
Generation of electricity from renewable sources has become a necessity, particularly due to environmental concerns. In order for renewable sources to provide reliable power, their sporadic availability under certain conditions and the lack of control over the resource must be addressed. Different renewable energy sources and storage technologies bring various properties to the table, and power systems must be adapted and constructed to accommodate these. Power electronics and micro-grids play key roles in enabling the use of renewable energy in the evolving smarter grids. This book, written by well-known researchers with broad expertise and successful publication records, provides a systematic overview of modern power systems with integrated renewable energy. Chapters provide concise coverage of renewable energy generation, of storage technologies including chemical, electrostatic and thermal storage systems, and of energy integration, power conditioning systems, economic dispatch and scheduling, EV integration, as well as communications and cyber-security in power systems. This work is a highly valuable resource for researchers in industry and academia involved with renewable energy technology and power systems, for advanced students of related subjects, and for utilities engineers and professionals.